Effect of breed and nutrition on performance of sheep in Tanzania - Mtenga, L.A.; Morungu, L.A.; Nyaki, F.P; Mgheni, M. (1981)
Limiting factors in sheep production in Tanzania are discussed. Due to lack of quantitative data effects of diseases and other factors, the paper partly attempts to quantify the performance of two breeds of sheep (Black Head Persian-BHP and Red Maasai-RM) under one government farm. Statistical comparison between these two breeds is presented on birth weight, weaning weight, mating weight and slaughter weight. Statistical comparison within these parameters is also discussed. The paper also discussed the performance of BHP and RM under controlled experimentation at the University Farm, Faculty of Agriculture, Forestry and Veterinary Science, Morogoro. Lambs at weaning were subjected to three treatments (grazing only S0; grazing with 100g concentrate supplementation per day- S1; and grazing with 500g concentrates supplementation per day- S2) for 5 months. Irrespective of level of supplementation BHP grew faster (84±10.6 g/day) than RM (59±7.3g/day). Body condition score and carcass weight were significantly higher in BHP than in RM; (3.1±1.14 and 12.22±1.364 kg for BHP and 2.4±0.96 and 8.47±1.48 kg for RM respectively. Generally, BHP tended to dress out higher (44.3±2.34%) than RM (42.9±4.95%) although the difference was not significantly significant. Supplementation improved liveweight gain significantly. Overall growth rates of lambs under S0, S1 and S2 treatments were 44±3.9, 61±8.8, and 109±11.6g respectively. Supplementation also improved the body condition score and dressing out percentage. The mean body condition scores and dressing out percentages were 1.7±0.61, 2.7±0.45, 3.9 ±0.76 and 39.1±9.33%, 42.1±2.05% and 49.6±2.43% respectively for S0, S1 and S2. The imporatnace of the results with emphasis on economics of supplementation is discussed.